Community Narratives in Producing Negative Images: Their Implications to Violent Extremism Recruitment (Asia Pacific Journal of Social Innovation, 2024)
This study explores how narratives within communities affected by the All-Out war of 2000 contribute to the creation and transmission of enemy images against the government. It examines the role of these stories in fostering a social identity that otherizes the government and discusses the mechanisms of vertical transmission of these images from parents to children. The paper also considers the implications of these narratives for recruitment into violent extremist groups and suggests strategies for reframing stories to mitigate their impact on borrowed trauma.